Relevances Of Promotion In Marketing Strategy - Umar Mohammed Ali (The American Journal of Management and Economics Innovations, 2021)
The study specifically is aimed at determining the relevance of promotion in marketing: an investigation on why companies promote their products. The study involves the relevance of promotion in marketing and impact of all promotional tools to every marketing activity. Promotion as one of the marketing mix element is important in understanding today’s success to marketing through endeavors on how to carefully implement it. It is very important to note that promotion is in existence for a very long period of time thoughout the world. The work carryout on relevance of promotion in marketing